Proverbs And Sayings As A Reflection Of National Character (Eurasian Journal of Humanities and Social Sciences, 2023)
This paper is devoted to the study of how proverbs and controversies reflect the character of a nation. The relevance of this topic is as follows: proverbs and controversies, being an integral part of the language, reflect the culture, identity, core values of the people. Therefore, the study of proverbs and controversies helps to understand the national characteristics of a given nation